Development of Catfish Cultivation Skills to Improve the Economy of “Garipinus” Catfish Farmers in Karanggebang, Jetis, Ponorogo - Kurniawan, Dhika Amalia; Etica, Use; Cahyani, Meitria; Ardiani, Yana Elita (Edumedia Solution, 2025)
The catfish farming grup “Garipinus” is a catfish farming grup in Karanggebang village, Jetis, Ponorogo. Catfish cultivation is an activity that has potential to develop the economy of the Karanggebang village community. The availability of catfish from the “Garipinus” breeder group is already quite plentiful, but it is still lacking in supplying market demand, because traded cannot take the catfish products within a short period of time, so it is necessary to increase knowledge and abilities in the productivity of catfish cultivation. The steps taken are to provide training and assinstence related to increasing the productivity of catfish cultivation. This program uses method of observation, socialization, training, and mentoring as well as menitoring and evaluation. The result of this activity is increased knowledge and ability of members of the “Garipinus” catfish cultivation and factors than influence increasing its productivity.